2013
DOI: 10.1021/jf300651d
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Hyaluronan Reduces Bone Turnover in Ovariectomized Rats

Abstract: The effect of oral hyaluronan (HA) on bone loss in ovariectomized (OVX) 3-month-old rats was measured using serum markers of bone turnover and bone mineral density. OVX rats were administered 1 mg/kg HA (OVX + HA) or phosphate-buffered saline (PBS) (OVX + PBS) by oral gavage (5 days/week for 54 days). Additional controls included sham ovariectomy with PBS gavage (Sham + PBS) and no treatment. Oral administration of HA resulted in approximately 50% (p < 0.05) increases in serum HA. Gel filtration analyses showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…However, it recovered to 94.48%, 77.59%, 77.87%, and 88.44% in RAL, CaCO 3 , CBP-Ca-L, and CBP-Ca-H groups, respectively. This suggested that CBP-Ca could effectively strengthen the mechanical properties of OVX rats [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it recovered to 94.48%, 77.59%, 77.87%, and 88.44% in RAL, CaCO 3 , CBP-Ca-L, and CBP-Ca-H groups, respectively. This suggested that CBP-Ca could effectively strengthen the mechanical properties of OVX rats [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…These characteristics contribute to the use of HA in cosmetics, medicines, and foods. Recently, orally administered HA was found to have beneficial functions in processes such as immune regulation, pain suppression, host defense, and bone metabolism (Asari and others ; Hill and others ; Tashiro and others ; Ma and others ). Therefore, polysaccharides have attracted attention as a functional food ingredient.…”
Section: Introductionmentioning
confidence: 99%
“…Gm-SGP improved the high bone turnover status in OVX rats Postmenopausal osteoporosis is closely characterized with simultaneous excessive increase in the rates of bone formation and bone resorption, leading to accelerated bone loss (Pacifici, 1996). Increasing studies have suggested that OVX-induced higher bone turnover rates can reflected by higher bone formation and resorption markers (Ma et al, 2013). Xia et al reported that Ca-SGP limited osteoporosis by reducing the expression of bone formation markers such as ALP, OCN, PICP, and BMP-2 as well as a bone resorption marker such as TRAP (Xia et al, 2015).…”
Section: Resultsmentioning
confidence: 99%